Business Analytical Capabilities and Artificial Intelligence-Enabled Analytics: Applications and Challenges in the Digital Era, Volume 1 - Musleh Al-Sartawi, Abdalmuttaleb M. A.; Aydiner, Arafat Salih; Kanan, Mohammad (Studies in Computational Intelligence, 2024)
XIII, 441 p. 39 illus., 22 illus. in color.